Usability of fractometer for the purpose of a practical preliminary assessment tool for wood density of Pinus brutia - Bilgin Icel (Maderas: Ciencia y Tecnología, 2024)
The fractometer is a device that breaks increment cores to measure fracture strength. The advantages of the device are that it is relatively fast, easy to use in the field, and it can perform direct strength measurements on increment cores. The main purpose of the study was to evaluate the usability of the fractometer as a preliminary evaluation tool for wood density traits of standing Turkish Pinus brutia (red pine) trees. Fracture strength was measured on 5 mm diameter increment cores, and X-ray densitometry was used for density measurements. Due to the high correlation between the two traits (fracture and density), a model was built using linear regression. Fifty trees were sampled to build the statistical model (r2: 0,74), and an equal sample size was used to test the model. The density value obtained from the model was 0,546 gcm-3, while the density value averaged by the X-ray method for the same group was 0,543 gcm-3. When considering mean values, it can be said that the model provides a good prediction. Based on personal experience and research results, some trees exhibited better growth and wood quality traits than others. Breeding from these trees could offer improvement in timber production and performance for Pinus brutia (red pine). As a general consequence, the fractometer and increment core sampling can be used for pine tree breeding programs for the preliminary assessment of wood density.